2010
DOI: 10.1037/a0019991
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of uncertainty as an indicator of effective leadership.

Abstract: Research and experience continue to reveal evolving modes of leadership behavior that challenge the practice of consulting psychology. Leadership development that has taken us beyond the notion of born leaders and stable environments has suggested that flexibility is vital. This may be partly because of the constant evolution of the organization and its leadership challenges, from command-and-control to paradigms that are participatory and recognize the importance of interpersonal skills, to an emerging paradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 18 publications
5
44
0
2
Order By: Relevance
“…Employees with a greater awareness of uncertainty and a better ability to deal with uncertain and uncontrollable situations were perceived as demonstrating more transformational leadership behaviors by their colleagues, independent of other individual differences. This finding is consistent with recent research on leadership and uncertainty (Cicero et al, 2010;White and Shullman, 2010). For instance, Cicero et al (2010) found that the degree to which leaders are prototypical of their groups was more strongly related to leadership success when employees experienced high levels of role ambiguity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Employees with a greater awareness of uncertainty and a better ability to deal with uncertain and uncontrollable situations were perceived as demonstrating more transformational leadership behaviors by their colleagues, independent of other individual differences. This finding is consistent with recent research on leadership and uncertainty (Cicero et al, 2010;White and Shullman, 2010). For instance, Cicero et al (2010) found that the degree to which leaders are prototypical of their groups was more strongly related to leadership success when employees experienced high levels of role ambiguity.…”
Section: Discussionsupporting
confidence: 90%
“…However, the positive relationship found between uncertainty management and transformational leadership is consistent with recent theorizing and empirical findings from other studies (Cicero et al, 2010;White and Shullman, 2010). Thus, organizational practitioners could train leaders so that they become better at recognizing and managing uncertainty.…”
Section: Practical Implications and Conclusionsupporting
confidence: 88%
See 1 more Smart Citation
“…Hodgson and White (2001) identified a set of behaviors characteristic of leaders who were viewed as having led successfully during periods of heighted ambiguity and concomitant uncertainty; these included (a) seeking mysteries, (b) tolerating risk, (c) future scanning, (d) tenacious challenging, (e) exciting and invigorating oneself and others, (f) flexibly adjusting, simplifying, and (g) focusing on the critical few. White and Shullman (2010) demonstrated the relationship of these behaviors to perceptions of leader success with an international pool of leaders. They found that the presence of these behaviors in dealing with ambiguity were positively correlated with leader success.…”
Section: Learning Leadership Approachesmentioning
confidence: 99%
“…It seems evident that in order to succeed, particularly at higher levels in an organization, there needs to be some level of comfort with ambiguous situations. White and Shullman (2010) propose that acceptance of ambiguity is an important indicator of the effectiveness of a leader; however, tolerance for ambiguity is rarely included as a critical trait for effective leaders (Heifetz, Grashow, & Linsky, 2009). …”
Section: Learning Agility and Individual Differencesmentioning
confidence: 99%